Prognostic biomarkers in primary progressive multiple sclerosis: Validating and scrutinizing multimodal evoked potentials. (May 2022) - Hardmeier, M.; Schlaeger, R.; Lascano, A.M.; Toffolet, L.; Schindler, C.; Gobbi, C.; Lalive, P.; Kuhle, J.; Kappos, L.; Fuhr, P.
Highlights: Combination of motor EP (MEP) from upper and lower limbs and somatosensory EP (SEP) after tibial nerve stimulation carries the main prognostic information predicting 32% of EDSS-change over two years in primary progressive multiple sclerosis (PPMS). Current results replicate and corroborate the previously reported prognostic value of multimodal EP in PPMS. Quantitative scoring outperforms ordinal scoring to prognosticate EDSS-change. Abstract: Objective: To validate the prognostic value of multimodal evoked potentials (mmEP) in primary progressive multiple sclerosis (PPMS) and to determine the most predictive EP-modalities. Methods: Thirty-nine patients with PPMS (expanded disability status scale (EDSS): 2.0–6.5; mean clinical follow-up: 2.8 years) had visual (VEP), upper and lower limb somatosensory (SEP) and motor EP (MEP) at baseline. Quantitative EP-scores for single (qVEP, qSEP, qMEP) and combined modalities were correlated to EDSS and compared to previously published data of 21 PPMS patients. Predictors of EDSS-change were analyzed in pooled data by linear regression. Results: Samples were comparable. Except qVEP, all EP-scores were correlated to EDSS at baseline (Rho: 0.45–0.69; p < 0.01) and follow-up (Rho: 0.59–0.80; p < 0.001). Combined EP-modalities significantly predicted EDSS-change (R 2 adj : 0.24), while EDSS and age did not. Tibial qSEP (R 2 adj : 0.22) and qMEP (R 2 adj : 0.26) were the best single modality predictors, outperformed by their combination (R 2 adj : 0.32). Conclusions: Quantitative EP-scores predict up to 32% of EDSS-change over three years. Modalities representing motor and long tract function carry the main prognostic information. Significance: Replication of previous results corroborates the use of mmEP as a prognostic biomarker candidate in PPMS.